The Role of Heat in Oxidation-Reduction Reactions: A Review: Peran Panas dalam Reaksi Oksidasi-Reduksi: Sebuah Tinjauan - Mohammed Mahdi Mohammed; Asam Hussein Ali (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Oxidation–reduction reactions are fundamental processes in chemistry and play essential roles in energy systems, biological processes, environmental chemistry, and metallurgical operations. Specific Background: Thermal energy is a critical factor that governs both thermodynamic feasibility and kinetic behavior in redox reactions, affecting reaction rates, equilibrium conditions, and electron transfer pathways. Knowledge Gap: Although the influence of temperature on chemical reactions has been widely recognized, a unified explanation connecting thermodynamic principles, kinetic theories, and practical redox applications across multiple scientific fields remains limited. Aims: This review summarizes how heat governs oxidation–reduction reactions by examining its effects on reaction thermodynamics, reaction kinetics, mechanistic pathways, and overall process performance. Results: The analysis of classical theories and published studies shows that temperature alters equilibrium constants, modifies activation energies, accelerates reaction rates, and affects electron transfer mechanisms. These thermal effects play significant roles in chemical systems including metallurgy, biological redox processes, environmental reactions, and emerging energy technologies. Novelty: The article synthesizes theoretical and applied perspectives to present an integrated view of thermal control in oxidation–reduction chemistry. Implications: Understanding the role of heat in redox reactions provides a conceptual foundation for improving chemical process design, optimizing reaction conditions, and guiding future research in electrochemistry, materials science, and energy conversion technologies. Keywords: Oxidation Reduction Reactions, Reaction Kinetics, Electron Transfer, Thermodynamic Equilibrium, Thermal Energy Key Findings Highlights Temperature modifies equilibrium behavior and activation barriers in redox systems Thermal conditions regulate electron exchange pathways during chemical transformations Multiple scientific fields apply temperature-controlled redox chemistry principles